The Role of Different Afferent Systems in the Modulation of the Otolith-Ocular Reflex After Long-Term Space Flights - Glukhikh, Dmitrii O.; Naumov, Ivan A.; Schoenmaekers, Catho; Kornilova, Ludmila N.; Wuyts, Floris L. (Frontiers in Physiology, 2022)
BACKGROUND: The vestibular (otolith) function is highly suppressed during space flight (SF) and the study of these changes is very important for the safety of the space crew during SF missions. The vestibular function (particularly, otolith-ocular reflex - OOcR) in clinical and space medicine is studied using different methodologies. However, different methods and methodologies can influence the outcome results. OBJECTIVE: The current study addresses the question of whether the OOcR results obtained by different methods are different, and what the role is of the different afferent systems in the modulation of the OOcR. METHODS: 25 Russian cosmonauts voluntarily took part in our study. They are crewmembers of long duration space missions on the International Space Station (ISS). Cosmonauts were examined in pre- and postflight "Sensory Adaptation" and “GazeSpin” experiments, twice before (preflight) and three times after SF (postflight). We used two different video oculography (VOG) systems for the recording of the OOcR obtained in each experiment. RESULTS: Comparison of the two VOG systems didn’t result into significant and systematic differences in the OOcR measurements. Analysis of the static torsion otolith–ocular reflex (OOR), static torsion otolith–cervical–ocular reflex (OCOR) and static torsion otolith–ocular reflex during eccentric centrifugation (OOREC) shows that the OOREC results in a lower OOcR response compared to the OOR and OCOR (before flight and late postflight). However, all OOcRs were significantly decreased in all cosmonauts early postflight. CONCLUSIONS: Analysis of the results of ocular counter rolling (OCR) obtained by different methods (OOR, OCOR and OOREC) showed that different afferent systems (tactile-proprioception, neck-cervical, visual and vestibular afferent input) have an impact on the OOcR.